2021
DOI: 10.33003/fjs-2021-0501-600
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Household’s Poverty Among Crop Farmers in Kaduna State, Nigeria

Abstract: This study examined the households’ poverty status among crop farmers in Kaduna State. Multi-stage sampling procedure was used to select 242 farmers for this study. Data were collected through using structured questionnaire with the help of trained enumerators. Descriptive and inferential statistics such as tobit regression and Foster, Greer and Thorbecke (FGT) model was employed in this study. The results showed that the mean age of the respondents was 45 years and were married, mean household size of the far… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
0
0
0
Order By: Relevance
“…This finding is in line with that of Abdulmumini et al (2019) who stated that the age population of the respondents in a similar study in Jigawa State was young and energetic that can affect the adoption of technologies. The result also agrees with the findings of Adamu et al (2021) who reported that young farmers in the productive age have the capacity of carrying out agricultural production.…”
Section: Socio-economic Characteristics Of Respondentssupporting
confidence: 92%
“…This finding is in line with that of Abdulmumini et al (2019) who stated that the age population of the respondents in a similar study in Jigawa State was young and energetic that can affect the adoption of technologies. The result also agrees with the findings of Adamu et al (2021) who reported that young farmers in the productive age have the capacity of carrying out agricultural production.…”
Section: Socio-economic Characteristics Of Respondentssupporting
confidence: 92%
“…fertilizer input) at affordable prices, and to sell their farm produce in bulk. According to Adamu et al (2021) membership in a cooperative association exposes women rice farmers to vital information as well as to access to production inputs. The sources of capital for rice production include the following: personal savings (72%), friends and family (16%), banks/ financial institutions (02%), cooperatives (8%), and money lenders (2%) (Figure 2).…”
Section: Institutional Variables Accessed By Women Rice Farmersmentioning
confidence: 99%
“…About 88% of the women rice farmers did not have access to credit facilities, while 12% had access. According to Adamu et al (2021) access to credit facilities will go a long way in improving the individual farm enterprises in terms of agricultural production. The access to agricultural credit by women rice farmers has the propensity to break the vicious cycle of poverty and raise the purchasing power of farm households.…”
Section: Institutional Variables Accessed By Women Rice Farmersmentioning
confidence: 99%
“…The States with the highest production (Taraba, Benue and Niger) are not those with the highest yields (Nassarawa, Osun, Ekiti, Ondo and Imo) (Adamu, Esheya, & Tanko, 2021). High production States have larger areas under cultivation, suggesting that yam production may be more intensive in the high yield States.…”
Section: Introductionmentioning
confidence: 96%